Description of the Implementation of Physical Education Learning for Children with Special Needs with Physical Disabilities at the Bukesra Special Needs School in Aceh - Zahara, Zahara; Zulfikar, Zulfikar; Iqram, Muhammad (Yayasan Insan Mulia Bima, 2025)
Physical Education, Sports, and Health (PJOK) isone of the compulsory subjects taught at the primary and secondary education levels in Indonesia. This study aims to determine how Physical Education, Sports, and Health (PJOK) learning is implemented for students with physical disabilities (Tuna Daksa) at SLB Bukesra Aceh. This research used a qualitative descriptive approach. Data were collected through interviews, observations, and documentation. The data were analyzed using three steps: data reduction, data presentation, and conclusion drawing. The research sample consisted of two classroom teachers and two students with physical disabilities. The results showed that PJOK learning at SLB Bukesra Aceh was running fairly well and adapted to the students’ abilities, although it was not yet optimal. Teachers used demonstration, practice, lecture, and question-and-answer methods. Evaluation was based on students’ abilities without a written assessment format. The main obstacles found were that teachers did not come from a physical education background, sports facilities were still limited, and parental support was not yet optimal. Therefore, training for teachers, the addition of disability-friendly sports facilities, and greater parental involvement are needed to improve PJOK learning for students with physical disabilities.